Education Contradiction Between City and Village - Atiatul Janah (Indonesian Journal of Education (INJOE), 2021)
Education is one of the most important things in human life. Every human being has the right to get a proper and equal education. However, what is happening in Indonesia is the inequality of education for all Indonesian citizens. Apart from that, recently, what has been discussed is the current education system in Indonesia which is considered rigid and ineffective. We can see this from the lagging quality of education in Indonesia compared to other countries. The education system used in Indonesia is not much different from the education system in other countries. The only difference is mistakes during practice in the field. There are many basic mistakes that make the gap between the goals of the education system and its implementation in the field. Which in the end makes all the goals can not be achieved and resolved properly. This study aims to determine the state of education between cities and villages in Indonesia and also the basic mistakes and solutions to all existing problems.